D = 1/ e - f , solve for F

is the work and answer

Multiply each side by e - f then you would have

d(e-f) = 1

Then

Divide by D

e-f = 1/d

Then Subtract e

-f = 1/d - e

Then multiply each side by -1

f = (-1/d) + e

Is this the answer?

Printable View

- Feb 21st 2011, 02:26 PMRush21125150D = 1/e-f sovle for F, Can someone see if i am correct?
D = 1/ e - f , solve for F

is the work and answer

Multiply each side by e - f then you would have

d(e-f) = 1

Then

Divide by D

e-f = 1/d

Then Subtract e

-f = 1/d - e

Then multiply each side by -1

f = (-1/d) + e

Is this the answer? - Feb 21st 2011, 02:27 PMAckbeet
Looks good to me. Probably a good idea not to mix upper-case and lower-case interchangeably throughout your derivations, though. It's clearer if you're consistent that way.

- Feb 21st 2011, 02:37 PMe^(i*pi)
It's also a good idea to make wise use of brackets. Your working is fine for D = 1/(e-f) but the question reads D = (1/e) - f